Unusual Observations in Leishmaniasis—An Overview - Priya Yadav; Mudsser Azam; V Ramesh; Ruchi Singh (Pathogens, 2023)
Leishmaniasis significantly affects the population of the tropics and subtropics. Clinical features and infective species of Leishmania are the primary factors driving the direction of diagnosis. The rise in incidences of atypical presentations present a challenge in patient treatment. Knowledge of unusual/rare presentations can aid in having a broader perspective for including the different aspects during the examination and thus avoid misdiagnosis. A comprehensive literature survey was performed to present the array of atypical presentations confounding clinicians which have been seen in leishmaniasis. Case reports of unusual findings based on the localizations and morphology of lesions and infective species and the predominant geographical sites over almost five decades highlight such presentations in the population. Information regarding the clinical features recorded in the patient and the chosen treatment was extracted to put forward the preferred drug regimen in such cases. This comprehensive review presents various unusual observations seen in visceral leishmaniasis, post-kala-azar dermal leishmaniasis, cutaneous leishmaniasis, and mucocutaneous leishmaniasis. It highlights the need to consider such features in association with differential diagnosis to facilitate proper treatment of the patient.